HyperThinking : Creating a New Mindset for the Age of Networks. - Weiss, Philip (Ashgate Publishing Ltd, 2012)
Over the last 14 years of advising leading global companies, author Philip Weiss developed a unique approach designed for the modern executive to adapt and thrive in this age of vast networks, digital communications and perpetual change. The Hyperthinking model is predicated on the assumption that the most important skill required to help you and your organization grow is the mind-set of individuals. Using the techniques in this book, practitioners will be able to continuously alter their perceptions and discover how to adapt to this new business world.